Timing of Chemotherapy and Radiotherapy Following Breast-Conserving Surgery for Early-Stage Breast Cancer: A Retrospective Analysis - Chen, Si-Ye; Tang, Yu; Wang, Shu-Lian; Song, Yong-Wen; Fang, Hui; Wang, Jian-Yang; Jing, Hao; Zhang, Jiang-Hu; Sun, Guang-Yi; Zhao, Xu-Ran; Jin, Jing; Liu, Yue-Ping; et al. (Frontiers in Oncology, 2020)
Purpose: To investigate the effect of chemotherapy and radiotherapy timing after breast conserving surgery (BCS) on recurrence and survival of women with early-stage breast cancer. Patients and methods: We retrospectively analysed 900 patients who underwent BCS followed by both adjuvant chemotherapy and radiotherapy. Of these, 488 women received chemotherapy first (CT-first group) while the other 412 received radiotherapy first (RT-first group). Locoregional recurrence (LRR), distant metastasis (DM), disease-free survival (DFS), and overall survival (OS) rates were calculated using the Kaplan-Meier method and further confirmed with propensity-score matching (PSM) and the Cox proportional hazards model. The optimal cut-off value of interval time from surgery to the start of chemotherapy was calculated by Maxstat. Results: The median follow-up was 7.1 years. In pre-match analysis, the CT-first group had a significantly higher 8-year DFS than the RT-first group (90.4% vs. 83.1%, P = 0.005). PSM analysis of 528 patients indicated that the 8-year DFS (91.0% vs. 83.3%, P = 0.005) and DM (8.6% vs. 14.6%, P = 0.017) were significantly better in the CT-first group, but that the OS (P =0.096) and LRR (P = 0.434) were similar. We found the optimal cut-off value of interval from surgery to chemotherapy was 12 weeks. Patients starting chemotherapy later than 12 weeks after surgery had significantly inferior survival outcomes. Conclusions: For women with breast cancer who require both chemotherapy and radiotherapy after BCS, adjuvant chemotherapy should be started within 12 weeks. Delaying the initiation of radiotherapy, for administration of long-course chemotherapy, does not compromise outcomes.